2020
DOI: 10.7150/ijms.44834
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of Korean propolis extract ameliorates DSS-induced colitis in BALB/c mice

Abstract: Inflammatory bowel disease (IBD) is a chronic disorder of the gastrointestinal tract characterized by inflammation. Although IBD is usually treated with anti-inflammatory agents, most of these treatments have limited efficacy. Propolis is a viscous mixture that honeybees produce by mixing saliva and honeycomb with exudate gathered from tree buds, sap flows, or other botanical sources. Although propolis has proved to ameliorate several inflammatory disorders, its therapeutic properties vary by geographical loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Other researchers have also reported that it is possible to induce a mouse model of acute experimental colitis models using methods similar to those reported in this study [39,40]. A series of studies have shown that food components have favorable ameliorative effects on acute colitis [8][9][10][11][12]. We conducted the first study on the attenuation of acute experimental colitis by OE.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Other researchers have also reported that it is possible to induce a mouse model of acute experimental colitis models using methods similar to those reported in this study [39,40]. A series of studies have shown that food components have favorable ameliorative effects on acute colitis [8][9][10][11][12]. We conducted the first study on the attenuation of acute experimental colitis by OE.…”
Section: Discussionmentioning
confidence: 57%
“…These alternative therapies are of great interest because of their low side effects [7]. Among these, algal oil [8], propolis extract [9], peptides derived from tuna [10], taurine [11], and astragalin [12] have been reported to exert protective effects against experimental colitis induced by dextran sulfate sodium (DSS) in mice. Thus, the potential exists for IBD patients to have a greater variety of substances that are effective, in the form of alternative treatments.…”
Section: Introductionmentioning
confidence: 99%
“…A handful of studies have already demonstrated that DSS-induced colonic damage is related to decreased gastric mucus content and secretion [ 33 ]. Therefore, we next evaluated if the protective effect of SDF could be associated with the maintenance of the colon's protective mucus barrier.…”
Section: Resultsmentioning
confidence: 99%
“…Stress. The inflammatory damage induced by DSS brought about the infiltration of neutrophils and macrophages, generating excessive amounts of reactive oxygen species with a subsequent increase in oxidative stress [33]. Therefore, we measured the GSH levels and SOD activity to quantify these parameters.…”
Section: Sdf Decreased Colonic Oxidativementioning
confidence: 99%
See 1 more Smart Citation